Characteristics of hospital pediatricians and obstetricians/gynecologists working long hours in Tokushima, Japan: A cross-sectional study - Nakagawa, Mai; Nakagawa, Kazumi; Nakai, Koga; Tominaga, Ayumu; Mori, Yoshiro; Iwasa, Takeshi; Urushihara, Maki; Hashimoto, Ichiro; Morioka, Hisayoshi (PloS one, 2024)
This study aimed to determine the actual working conditions, including working hours and desired future working styles of hospital pediatricians and obstetricians/gynecologists (OB/GYNs) in Tokushima Prefecture. This cross-sectional study used a self-administered questionnaire. Pediatricians and OB/GYNs (n = 96) working at 14 hospitals in Tokushima Prefecture were surveyed. The questionnaire included items related to working hours, working status, number of medical institutions, task-shifting/task-sharing status, and preferred work style. Factors associated with work hours were analyzed. Approximately 40% and 10% of pediatricians and OB/GYNs worked ≥60 h/week and ≥80 h/week, respectively. Their weekly working hours were significantly positively associated with the number of nights and holidays worked and concurrent medical facilities they worked at. Multiple regression models showed that weekly working hours were significantly associated with working at night and day-off duties and the number of working medical institutions being worked at concurrently. Pediatricians and OB/GYNs who worked ≥60 h/week were not implementing a "multiple attending physician system" or "on-call system," and task-shifting/task-sharing was inadequate. A significantly higher proportion of physicians who worked long hours (≥60 h/week or ≥80 h/week) wanted to reduce the number of night and day-off duties and work hours compared with those who did not. The results of this study suggest that many pediatricians and OB/GYNs work long hours, and it is essential to improve their work environment, including task-shifting/task-sharing. Further enhanced recruitment and retention of hospital pediatricians and OB/GYNs is required. A detailed and large-scale study of pediatricians and OB/GYNs' working environments is essential in the future.